Effects of Bacillus licheniformis on Growth Performance, Diarrhea Incidence, Antioxidant Capacity, Immune Function, and Fecal Microflora in Weaned Piglets - Xiaorong Yu; Zhenchuan Cui; Songke Qin; Ruiqiang Zhang; Yanping Wu; Jinsong Liu; Caimei Yang (Animals, 2022)
Bacillus licheniformis (B. licheniformis) is a safe probiotic that can promote animal growth and inhibit pathogenic bacteria. This study aimed to assess the effects of B. licheniformis, one green feed additive, on growth performance, diarrhea incidence, immune function, fecal volatile fatty acids, and microflora structure in weaned piglets. Weaned piglets (n = 180) were randomly divided into three treatment groups and fed a basal diet and a basal diet supplemented with 500 mg B. licheniformis per kg and 1000 mg B. licheniformis per kg, respectively. The dietary 500 mg/kg B. licheniformis inclusion improved the average daily gain, reduced diarrhea incidence, and strengthened antioxidant capacity. Piglets supplemented with B. licheniformis presented increased serum immunoglobulins (IgA, IgM) compared to the CON group. Meanwhile, the expression of anti-inflammation factors was increased, and the levels of pro-inflammation factors were reduced after B. licheniformis administration. Moreover, the levels of volatile fatty acids, including acetic acid, propionic acid, butyric acid, isobutyric acid, and isovaleric acid, in the BL500 and BL1000 groups were increased compared with the CON group, and the concentration of valeric acid was higher in the BL500 group. Furthermore, piglets in the 500 mg/kg B. licheniformis addition group significantly altered fecal microbiota by increasing Clostridium_sensu_stricto_1 and Oscillospira. In conclusion, dietary B. licheniformis relieved diarrhea, enhanced antioxidant capacity, immunity function, and fecal microflora structure in weaned pigs.